Outcomes of percutaneous cholecystostomy and predictors of eventual cholecystectomy. (10th December 2015) - Yeo, Charleen Shan Wen; Tay, Vivyan Wei Yen; Low, Jee Keem; Woon, Winston Wei Liang; Punamiya, Sundeep J; Shelat, Vishal G
Abstract: Background: Percutaneous cholecystostomy (PC) is an established treatment for high surgical risk patients with acute cholecystitis. This paper studies factors predictive of mortality and eventual cholecystectomy. Methods: A retrospective review of all patients who underwent PC from March 2005 to March 2015 was performed. Patient demographics, clinical features, comorbidity profile, grade of cholecystitis, interval between cholecystitis diagnosis and PC, and method of PC were studied. Length of stay, complications, readmission rate, mortality and eventual cholecystectomy were studied. For patients with eventual cholecystectomy, operative data and perioperative outcomes were studied. Results: One hundred and three patients with median age of 80 years (range 43–105) underwent PC. Median interval to PC was 2 days (range 0–15). 9.7% of patients had complications. Median length of stay was 19 days (range 3–206). 41% underwent eventual cholecystectomy. 30‐day mortality rate was 10.7%. Higher APACHE II scores ( P = 0.004), higher Charlson comorbidity index (CCI) ( P = 0.009), and longer interval from diagnosis to PC ( P = 0.037) were associated with in‐hospital mortality. Younger age ( P = 0.015), lower APACHE II scores ( P = 0.043) and lower CCI ( P = 0.002) were associated with eventual cholecystectomy. Conclusion: Percutaneous cholecystostomy is safe and effective in treatment of acute cholecystitis. Prompt PC improves survival in high risk surgical patients. Comorbidity severity is associated with mortality. Patients with lesser comorbidity are likely to receive eventual cholecystectomy.